Children's lives and schooling across societies - Hannum, Emily; Fuller, Bruce (Research in sociology of education ;, 2006)
In recent decades, sociological research has investigated the nature of the school institution and its uneven effects on the progress of families, societies, and the global community. Yet, relatively little comparative research on schooling has dealt in a serious way with links between schooling and the other major contexts of childhood: families and communities. This edition of "Research in the Sociology of Education" speaks to the diverse contexts in which children function around the world, and to how these contexts shape school experiences and outcomes. The edition's authors are international and interdisciplinary. They offer a pastiche of perspectives on a single topic: how the non-school contexts of childhood interact with the school institution to advance modern and not-so-modern forms of virtue, merit, and attainment, in cultural context. This book offers qualitative and statistical portraits of children living in Asian and African countries. It links educational opportunities to the child's socialization. It urges social scientists and policy makers to consider a child's surroundings when modeling the modern school system. This book series is available electronically online.